Earthquake preparedness and response for nuclear power plants - Godoy, Antonio R.; Sollogoub, Pierre; Chigama, A. (International Atomic Energy Agency, 2011)
"This Safety Report provides up to date detailed guidance on actions to be taken in preparation for, and following, an earthquake at a nuclear power plant, taking into account the gained knowledge and experience of Member States from the occurrence of strong earthquakes that affected nuclear power plants up to 2010. The publication is a compilation of available references based on related standards and proposes a more comprehensive set of criteria than the existing ones in some national regulations, based on damage and earthquake exceedance levels for dealing with situations related to plant shutdown, plant restart or plant continuing operation following the occurrence of an earthquake which may exceed the original design level. It will be a useful tool for regulatory bodies, specialists on earthquake engineering and technical support organizations."--Publisher description.
Title screen viewed on October 11, 2012.
"May 2011."
"STI/PUB/1473"--Title page verso.
"The IAEA officers responsible for this publication were A. Godoy, P. Sollogoub and A. Chigama of the Division of Nuclear Installation Safety."--Foreword.
Available on the Internet in PDF format.
Keywords: Nuclear power plants -- Earthquake effects -- Safety measures.; Nuclear power plants -- Risk assessment.; Earthquake resistant design -- Safety regulations.; Earthquake hazard analysis.; elektronické knihy; electronic books